Cognitive style and Students’ academic achievement: a meta-analysis - Xie, Qun; Yang, Kaihua; Ji, Ran; Qian, Yujing; Tong, Linjia; Chao, Chih Nuo Grace; Sin, Kuen Fung (Frontiers in Education, 2025)
This study investigates the relationship between field independence and dependence on cognitive style and student academic achievement. A meta-analysis was conducted on 42 studies related to this topic. The findings reveal a significant positive correlation between field independence and dependence on cognitive style and academic achievement among primary and middle school students (r = 0.308, p < 0.01). Subgroup analyses further indicate that factors such as the cognitive style measurement instrument (QB = 111.347, p < 0.01), subject area (QB = 71.652, p < 0.01), and academic achievement type (QB = 35.083, p < 0.01) significantly moderate this relationship. However, gender (QB = 2.771, p > 0.01) and educational stage (QB = 5.952, p > 0.01) do not appear to have a significant impact on the effect size. These findings highlight the importance of considering methodological and contextual factors when examining the influence of cognitive style on academic performance. Future research should explore potential mechanisms underlying these relationships to inform more effective educational strategies.